Experimental and theoretical characterization of Dy-doped hydroxyapatites - Isen, Fatih; Kaygili, Omer; Bulut, Niyazi; Ates, Tankut; Osmanlioglu, Fatih; Keser, Serhat; Kareem, Rebaz Obaid (Springer, 2023)
The effects of adding Dy to the hydroxyapatite (HAp) structure were investigated experimentally and theoretically. The as-obtained experimental results with an increasing amount of Dy are as follows. X-ray diffraction, Raman, and Fourier transform infrared measurements verified the HAp structure for each specimen. The crystallinity, lattice parameters, lattice stress, strain, and anisotropic energy density were affected. Thermal stability and stoichiometry were not affected. It was observed that all the Dy-doped HAps have smaller crystallite size values compared to the un-doped HAp. The cell viability obtained from mouse fibroblast cell (L929) was higher than 82%, indicating all the samples were biocompatible. The theoretical findings, obtained from the density functional theory (DFT) calculations, exhibited a continuous decrease in the bandgap from 4.7109 to 3.7982 eV, an increase in the density from 3,155 to 3,189 kg m(-3), and an increase in the linear absorption coefficient.
Keywords: Hydroxyapatite; Dysprosium (Dy); Band structure